An improved method for the incorporation of fluoromethyl ketones into solid phase peptide synthesis techniques. Issue 33 (8th June 2021) - Joshi, Dhira; Milligan, Jennifer C.; Zeisner, Theresa U.; O'Reilly, Nicola; Diffley, John F. X.; Papageorgiou, George
Abstract : An improved and expedient technique for the synthesis of peptidyl-fluoromethyl ketones is described. Abstract : An improved and expedient technique for the synthesis of peptidyl-fluoromethyl ketones is described. The methodology is based on prior coupling of an aspartate fluoromethyl ketone to a linker and mounting it onto resin-bound methylbenzhydrylamine hydrochloride. Subsequently, by utilising standard Fmoc peptide procedures, a number of short Z-protected peptides were synthesised and assessed as possible inhibitors of the main protease from SARS-CoV-2 (3CL pro ).